The Impact of High-Pressure Processing on Physicochemical Properties and Sensory Characteristics of Three Different Lamb Meat Cuts - Qianli Ma; Nazimah Hamid; Indrawati Oey; Kevin Kantono; Mustafa Farouk (Molecules, 2020)
This study investigated the effects of high pressure processing (HPP) on the physicochemical properties and sensory characteristics of different lamb meat cuts. Lamb meat discolouration occurred when HPP was applied at 400 and 600 MPa. Thiobarbituric acid reactive substances (TBARS) values significantly increased with pressure increase from 200 to 600 MPa for loin cut, and 300 to 600 MPa for shoulder and shank cuts. Saturated fatty acid and polyunsaturated fatty acid content significantly decreased with pressure increase from 200 to 600 MPa for shank and shoulder cuts, and 300 to 600 MPa for loin cut. Free amino acids content significantly increased in shank and loin cuts with pressure increase after 200 MPa, and in shoulder cuts after 400 MPa. In addition, samples treated with HPP at high pressure levels of 400 and 600 MPa were associated with browned, livery and oxidized flavours. The pressure levels applied and type of cuts used are important considerations during HPP processing as they influenced physicochemical and sensory properties of lamb samples.